Capital social do BOARD e desempenho de empresas de capital aberto - Aranha, Cézar Eduardo (2013)
This study seeks to assess how social capital of the board influences the performance of companies listed on the BM&F Bovespa, in the period 2010-2011. To achieve this goal we define as the performance indicator the market value and cost of capital. Through the position and the capital of the board of directors in corporate network relationships, we seek to answer the research question using the convergence of social network analysis methods and analysis of panel data. The capital of the board was measured from the resources immersed in direct relationships, indirect relations and heterogeneous relations of the board, in which we take as a proxy the resources of the market value of relationships. Thus, this study showed that the position of the board on the network did not influence corporate performance indicators by market value and cost of capital.Also shows that social capital of the board influence the market value of companies through direct relationships and heterogeneous relations, whose greater access to capital immersed in relations is associated with increased market value of companies. The capital of the board was also significant in reducing the cost of capital of companies through direct relations, relations and indirect relations heterogeneous, in that the higher the capital available for the network of relationships in an organization, the less cost of capital of listed companies traded. This study comes to the conclusion that the position of the board on the network does not influence the performance of listed companies, but the capital of this advice points to influence the performance of listed companies where an increase of this capital increases the value corporate market and reduces the cost of capital of companies, this study also provides a gain to science to analyze the capital through the resources embedded in the network bringing empirical envidências how these features influence the market value and cost of capital companies listed on the BM&F Bovespa.